Using 13C‐NMR dereplication to aid in the identification of xanthones present in the stem bark extract of Calophyllum brasiliense. Issue 6 (2nd May 2021) - Silva‐Castro, Lina Fernanda; Derbré, Séverine; Le Ray, Anne Marie; Richomme, Pascal; García‐Sosa, Karlina; Peña‐Rodriguez, Luis Manuel
Abstract: Introduction: Xanthones are metabolites with a variety of biological properties. The Clusiaceae family, which until recently included the genus Calophyllum, is recognised for its production of monohydroxylated and polyhydroxylated xanthones. Presently, C. brasiliense is the only Calophyllum spp. known to occur in the Yucatan peninsula. Objective: To use a combination of traditional phytochemical methods and carbon‐13 nuclear magnetic resonance ( 13 C‐NMR) dereplication analysis to identify xanthones in the stem bark of C. brasiliense . Material and methods: Initial fractionation and purification of the stem bark extract of C. brasiliense produced macluraxanthone (1 ). Additional xanthones, together with chromanones and terpenoids, were identified using 13 C‐NMR dereplication analysis in different semipurified fractions obtained from the low and medium polarity fractions of the stem bark extract of C. brasiliense . Results: Initial identification of macluraxanthone (1 ) was confirmed by 13 C‐NMR dereplication analysis; additionally, 13 C‐NMR dereplication analysis allowed the identification of a number of monohydroxylated and polyhydroxylated xanthones, together with chromanones and terpenoids. Conclusion: This study confirms C. brasiliense as a rich source of xanthones and the 13 C‐NMR dereplication analysis as a suitable method to quickly identify the presence of different families of secondary metabolites in semipurified fractions. Abstract : Calophyllum brasiliense is recognised for its production of xanthones having different biological activities. In this investigation, a combination of phytochemical methods and carbon‐13 nuclear magnetic resonance ( 13 C‐NMR) dereplication analysis allowed the identification of a number of monohydroxylated and polyhydroxylated xanthones, together with chromanones and terpenoids, from the stem bark extract of the plant.